Influence of ethanol-biodiesel blends on diesel engines combustion behavior and particulate matter physicochemical characteristics. (December 2022) - Karin, Preechar; Tripatara, Aphichai; Wai, Phyo; Oh, Ban-Seok; Charoenphonphanich, Chinda; Chollacoop, Nuwong; Kosaka, Hidenori
Abstract: Ethanol-blended biodiesel fuel can reduce smoke emissions by over 50% on both a single-cylinder engine and a four-cylinder engine. The average single primary particle size of biodiesel blended diesel, biodiesel, and ethanol blended biodiesel soot are approximately 30, 27, and 29 nm, respectively. The maximum graphene fringe length of biodiesel blended diesel, biodiesel, and ethanol blended biodiesel CI engine's soot are approximately 5.2, 4.6, and 4.5 nm. The carbon atom density of soot particles emitted from the diesel, biodiesel, and ethanol blended biodiesel CI engines are approximately 102, 91, and 88 atoms/nm3.